Hyperboles We Live by [?] (Proceedings of Southern Federal University. Philology, 2017)
Grigory G. Khazagerov (Rostov-on-Don, Russian Federation)The article treats the phenomenon of hyperbole as a test which allows, on the one hand, to see the weakness of the cognitive approach adopted today for the study of the trope, on the other hand, the strengths of rhetorical view of the trope. The idea that rhetoric tropes were mere embellishments of speech is challenged. The role of tropes in cultivation of language and communicative space is underlined. Metaphor and hyperbole are seen as tropes which, are most closely connected with the cultural context and language conventions. The connection between these tropes is demonstrated by the example of antonomasia. From a rhetorical point of view both metaphors and hyperboles set cultural standards. The paradox of hyperbole is that when dealing with a homogeneous object, at the same time it does not enter into an active interaction with it (with a certain maximum or minimum), while the metaphor when dealing with heterogeneous entity actively interacts with the domain involved, which is reflected in the cognitive approach. Consequently, in the hyperbole the role of unconsciously perceived social guide is reduced, while the role of reference, helping us to build communication is strengthened. A marker of conventionality is contained in the very nature of hyperbole. In metaphor we see the opposite picture. However, in the metaphor there are markers of conventionality (in some of its forms or contexts), and this makes its social role similar to the social role of hyperbole. Both rhetorical and cognitive approaches recognize the social role of the trope. But the rhetorical approach, focused on the development of communicative space is invariant with respect to the tropes and contexts of their use. After decline of rhetoric the cognitive approach, focused on the mapping of mental space, and restored trope’s social role. The approach has a varying degree of relevance for different tropes and their contexts.Key words: metaphor, hyperbole, cognitive approach, rhetorical approachDOI 10.23683/1995-0640-2017-3-45-55